Efficient acute and chronic infection of stem cell-derived hepatocytes by hepatitis C virus. Issue 9 (29th February 2020) - Carpentier, Arnaud; Sheldon, Julie; Vondran, Florian W R; Brown, Richard JP; Pietschmann, Thomas
Abstract : Objective and design: Human stem cell-derived hepatocyte-like cells (HLCs) have shown high potential as authentic model for dissection of the HCV life cycle and virus-induced pathogenesis. However, modest HCV replication, possibly due to robust innate immune responses, limits their broader use. To overcome these limitations and to dissect the mechanisms responsible for control of HCV, we analysed expression of key components of the interferon (IFN) system in HLCs, assessed permissiveness for different HCV strains and blocked innate immune signalling by pharmacological intervention. Results: Transcriptional profiling revealed that HLCs constitutively express messenger RNA of RLRs, and members of the IFN pathway. Moreover, HLCs upregulated IFNs and canonical interferon-regulated genes (IRGs) upon transfection with the double-stranded RNA mimic poly(I:C). Infection of HLCs with Jc1-HCVcc produced only limited viral progeny. In contrast, infection with p100, a Jc1-derived virus population with enhanced replication fitness and partial resistance to IFN, resulted in robust yet transient viraemia. Viral titres declined concomitant with a peak of IRG induction. Addition of ruxolitinib, a JAK/STAT inhibitor, permitted chronic infection and raised p100 infectious virus titres to 1×10 5 FFU/mL. IRGs expression profiling in infected HLCs revealed a landscape of HCV-dependent transcriptional changes similar to HCV-infected primary human hepatocytes, but distinct from Huh-7.5 cells. Withdrawal of ruxolitinib restored innate immune responses and resulted in HCV clearance. Conclusion: This authentic human cell model is well suited to examine acute and chronic host-HCV interactions, particularly IFN-triggered antiviral effector functions and mechanisms of innate immune control of HCV infection.